The sea peoples and their world : a reassessment - Oren, Eliezer D. (Philadelphia : University Museum, 2000)
This volume presents the results of the 1995 international seminar on the history and archaeology of the Sea Peoples. The 17 comprehensive articles, written by leading scholars in the fields of Egyptology, Hittitology, biblical studies, and Aegean, Anatolian, and Near Eastern archaeology, examine current methodologies and interpretations concerning the origin, migration, and settlement of the Sea Peoples against the overwhelming new archaeological record from sites throughout the Mediterranean basin and the Levant. Symposium Series 11University Museum Monograph, 108.
Cultural innovations in Cyprus relating to the Sea Peoples / Vassos Karageorghis -- Mycenaean IIIC:1b and related pottery in Cyprus : comments on the current state of research / Barbara Kling -- Aegean and the origin of the Sea Peoples / Philip P. Betancourt -- Western Mediterranean overview : peninsular Italy, Sicily and Sardinia at the time of the Sea Peoples / Lucia Vagnetti -- Early Iron Age at Gordion : the evidence from the Yassihöyük stratigrahic sequence / Mary M. Voigt and Robert C. Henrickson.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Sea Peoples; Mediterranean Region -- Antiquities; Mediterranean Region -- History; Middle East -- Antiquities; Middle East -- History -- To 622.; Peuples de la Mer; Méditerranée, Région de la -- Histoire; Moyen-Orient -- Antiquités.; Moyen-Orient -- Histoire -- Jusqu'à 622.; 15.51 Antiquity; Antiquities; Sea Peoples; Mediterranean Region; Middle East; !!!GESPERRT!!!Seevölker; Zeevolken; Archeologische aspecten; Sea Peoples; Mediterranean Region -- Commerce -- To 500.; Middle East -- Antiquities; Middle East -- History -- To 622.; To 622; History; Congresses (form)